Air-coupled ultrasound and electrical impedance analyses of normally dried and thermally modified Scots pine (Pinus sylvestris). Issue 5 (19th October 2016) - Tomppo, Laura; Tiitta, Markku; Lappalainen, Reijo
Abstract: Wood is graded according to strength in various applications. The ultimate strength can only be determined by breaking the specimen, and thus other characteristics like density and modulus of elasticity (MOE) are used for estimation of the strength. In this study, the properties of normally dried and thermally modified Scots pine were studied using electrical impedance and air-coupled ultrasound (ACU) methods. Density, hardness, MOE and strength were analysed and compared with the electrical and ultrasonic responses. The measurements were conducted in stable laboratory conditions with well equilibrated samples and the moisture content was not determined. Both the ultrasonic and electrical parameters correlated with the density and mechanical properties. Using multivariate analysis, density could be estimated with accuracy of 21 kg/m 3 (SD) for normally dried timber and 13 kg/m 3 (SD) for thermally modified timber ( TMT; N = 15). MOE could be estimated with accuracy of 0.7 kN/mm 2 (SD) for normally dried timber and 1 kN/mm 2 (SD) for TMT ( N = 14). According to the study, electrical impedance spectroscopy combined with ACU measured across the grain is a potential non-destructive technique for the strength estimation of wood.